Benign Recycling of Spent Batteries towards All‐Solid‐State Lithium Batteries. Issue 38 (6th June 2019) - Wang, Yao‐Yao; Diao, Wan‐Yue; Fan, Chao‐Ying; Wu, Xing‐Long; Zhang, Jing‐Ping
Abstract: Lithium‐ion batteries (LIBs) are one of the most significant energy storage devices applied in power supply facilities. However, a huge number of spent LIBs would bring harmful resource waste and environmental hazards. In this study, a benign hydrometallurgical method using phytic acid as precipitant is proposed to recover useful metallic Mn ions from spent LiMn2 O4 batteries. Besides Mn‐based cathodes, this recovery process is also applicable for other commercial batteries. More importantly, for the first time, the as‐obtained manganous complex is employed as a nanofiller in a polyethylene oxide matrix to largely improve Li + conductivity and transference number. As a result, when applied in all‐solid‐state lithium batteries, high capacity and outstanding cyclic stability are achieved with capacity retention of 86.4 % after 60 cycles at 0.1 C. The recovery of spent lithium batteries not only has benefits for the environment and resources, but also shows great potential application in all‐solid‐state lithium batteries, which opens up a costless and efficient circulation pathway for clean and reliable energy storage systems. Abstract : Come full circle : The product recovered from a spent LiMn2 O4 battery is converted into a solid polymer electrolyte for high‐performance lithium metal batteries. This opens up a costless and efficient circulation pathway for clean and reliable energy storage systems